Biallelic AOPEP Loss‐of‐Function Variants Cause Progressive Dystonia with Prominent Limb Involvement. Issue 1 (1st October 2021) - Zech, Michael; Kumar, Kishore R.; Reining, Sophie; Reunert, Janine; Tchan, Michel; Riley, Lisa G.; Drew, Alexander P.; Adam, Robert J.; Berutti, Riccardo; Biskup, Saskia; Derive, Nicolas; Bakhtiari, Somayeh; et al.
ABSTRACT: Background: Monogenic causes of isolated dystonia are heterogeneous. Assembling cohorts of affected individuals sufficiently large to establish new gene–disease relationships can be challenging. Objective: We sought to expand the catalogue of monogenic etiologies for isolated dystonia. Methods: After the discovery of a candidate variant in a multicenter exome‐sequenced cohort of affected individuals with dystonia, we queried online platforms and genomic data repositories worldwide to identify subjects with matching genotypic profiles. Results: Seven different biallelic loss‐of‐function variants in AOPEP were detected in five probands from four unrelated families with strongly overlapping phenotypes. In one proband, we observed a homozygous nonsense variant (c.1477C>T [p.Arg493*]). A second proband harbored compound heterozygous nonsense variants (c.763C>T [p.Arg255*]; c.777G>A [p.Trp259*]), whereas a third proband possessed a frameshift variant (c.696_697delAG [p.Ala234Serfs*5]) in trans with a splice‐disrupting alteration (c.2041‐1G>A). Two probands (siblings) from a fourth family shared compound heterozygous frameshift alleles (c.1215delT [p.Val406Cysfs*14]; c.1744delA [p.Met582Cysfs*6]). All variants were rare and expected to result in truncated proteins devoid of functionally important amino acid sequence. AOPEP, widely expressed in developing and adult human brain, encodes a zinc‐dependent aminopeptidase, a member of a class of proteolytic enzymes implicated in synaptogenesis and neural maintenance. The probands presented with disabling progressive dystonia predominantly affecting upper and lower extremities, with variable involvement of craniocervical muscles. Dystonia was unaccompanied by any additional symptoms in three families, whereas the fourth family presented co‐occurring late‐onset parkinsonism. Conclusions: Our findings suggest a likely causative role of predicted inactivating biallelic AOPEP variants in cases of autosomal recessive dystonia. Additional studies are warranted to understand the pathophysiology associated with loss‐of‐function variation in AOPEP . © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society